The use of the semantic differential in cross-cultural research - Taylor, D. M.; Dagot, E. P.; Gardner, R. C. (Philippine Journal of Psychology, 1969)
Two groups of English-Tagalog bilinguals rated each of eight ethnic group labels on the same 48 semantic differential scales. One-hundred-and-two Ss responded in English while a second group of 111 Ss was administered an identical form of the scales prepared in Tagalog by means of a back-translation procedure. The results indicated that there was moderate agreement between the factor structures of the ratings on both forms of the scales. In terms of responses on individual scales it seemed clear that the Ss who responded in their native language (Tagalog) were more willing to express themselves evaluatively than those Ss who made their ratings on the English form.